Open for business : Russia's return to the global economy - Hewett, Edward A. (Brookings Institution, 1992)
In December 1991 the Union of Soviet Socialist Republics--born in violent revolution and dominated for more than six decades by highly authoritarian rule--was dissolved by its constituent republics. The causes for this remarkable event will be probed for many years to come. Our understanding of it may never be complete. Nevertheless, it is evident even now that part of the story lay in a conscious redirection of policy by specific individuals. Those at the center of political and economic power understood the flaws in their system well enough to initiate a process of reform, but one that trigg.